Follow or not? Descriptive norms and public health compliance: Mediating role of risk perception and moderating effect of behavioral visibility - Zhang, Shuwei; Wang, Yan; Wei, Yujie (Frontiers in Psychology, 2022)
In a pandemic context, public health events are receiving unprecedented attention, and identifying ways to enhance individual public health compliance behaviors has become an urgent practical problem. Considering that individual decisions are susceptible to group members’ behaviors and that descriptive norms provide social information about the typical behaviors of others, we focused on the effects of the properties and reference groups of descriptive norms on public health compliance behaviors. We also investigated the mechanism with risk perception as a mediator and the applicable condition with behavioral visibility as a moderator. Through a 2 × 2 × 2 between-subject survey experiment with 529 subjects, we demonstrated that (1) compared with the negative norm, the positive norm was more effective in promoting public health compliance behaviors; (2) compared with the distal group norm, the proximal group norm more significantly promoted public health compliance behaviors; (3) the effect of the property of descriptive norms on public health compliance behaviors was weakened in the treatment of the proximal group norm; (4) risk perception partially mediated the association between the property of descriptive norms and public health compliance behaviors and fully mediated the effect of the interaction of the property and the reference group of descriptive norms on public health compliance behaviors; in the treatment of the negative-proximal group norm, individuals perceived more risk, thus effectively nudging their public health compliance behaviors; (5) compared with low-visibility behaviors, public health compliance behaviors were significantly stronger for high-visibility behaviors; (6) the property of descriptive norms had a weaker effect on public health compliance behaviors for low-visibility behaviors. In terms of theoretical significance, we refined the study of descriptive norms to promote the application of behavioral public health policy. Moreover, the new model of public health compliance behaviors constructed in this study explains the mechanism and applicable conditions of public health compliance behaviors. In practical terms, this study has implications for designing intervention programs to nudge public health compliance behaviors.